Value Addition to Grasshopper Products through Processing and Marketing Development Strategies - Hengsrisombat, Jirasak; Phimpho, Phanni (Rajapark Journal, 2024)
This research aimed to study the value addition of grasshopper products through processing, analyze the marketing factors that influence value creation, and develop appropriate strategies for processed grasshopper products. The sample included 432 consumers who had previously consumed insects in Sa Kaeo Province and 30 key informants, totaling 462 participants. Data were collected using a questionnaire with a reliability coefficient of 0.84. Statistical analysis included descriptive statistics such as mean and standard deviation, as well as inferential statistics including t-test, One-way ANOVA, and Pearson Chi-Square. The research findings revealed that the value addition to grasshopper products through processing and the marketing factors influencing consumption and purchasing decisions were significantly correlated, with a Pearson Chi-Square value of 33.989 and a significance level of 0.000*. Additionally, the perception of grasshoppers as highly nutritious was significantly related to the purchasing decision, with a Pearson Chi-Square value of 19.18 and a significance level of 0.000*. The marketing mix factors influencing value addition were ranked as follows: marketing promotion and product were at a high level, distribution channels were at a high level, and price was at a moderate level. The comparison of satisfaction with distribution channels between male and female respondents showed a significant difference at the 0.05 level. The strategy for developing processed grasshopper products included creating a dried grasshopper seasoning with a green cap sauce flavor that is familiar to consumers, as well as designing packaging that clearly represents the product and its flavor.